2010
DOI: 10.1002/j.1551-8833.2010.tb10055.x
|View full text |Cite
|
Sign up to set email alerts
|

The institutional politics of water conservation

Abstract: This article analyzes the influence of local governmental structures on the likelihood that utilities adopt one of two water conservation policies: conservation rates and landscape audits. Statistical analysis tests the effects of special‐district versus general‐purpose‐structures, ward‐based versus at‐large electoral structures, and mayor‐council versus council‐manager charter forms. The results demonstrate that government institutions influence adoption of conservation policies in predictable ways, even afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 15 publications
0
46
0
Order By: Relevance
“…These results are broadly consistent with previous studies that have explored economic factors. Teodoro [2010] analyzed two policies, landscape audits and rate structure, and found that higher moisture index and groundwater use were positively associated with both policies and that higher median income was positively associated with rate structure policy. In a study of utility rates, Rahill-Marier and Lall [2013] found that groundwater was Water Resources Research 10.1002/2015WR016943 the least costly source and that use of diverse sources is very costly, although they also found indications that this is changing and that in some markets groundwater may soon become even more expensive than nontraditional sources, such as desalination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are broadly consistent with previous studies that have explored economic factors. Teodoro [2010] analyzed two policies, landscape audits and rate structure, and found that higher moisture index and groundwater use were positively associated with both policies and that higher median income was positively associated with rate structure policy. In a study of utility rates, Rahill-Marier and Lall [2013] found that groundwater was Water Resources Research 10.1002/2015WR016943 the least costly source and that use of diverse sources is very costly, although they also found indications that this is changing and that in some markets groundwater may soon become even more expensive than nontraditional sources, such as desalination.…”
Section: Discussionmentioning
confidence: 99%
“…Rather than focus on what type of water conservation policy is better than another, our approach begins with a broad descriptive and explanatory question about the range of water conservation policies: what are the conditions-social, political, economic, hydrological, and technological-that facilitate or impede transitions to an integrated water management regime with highly developed conservation measures? Previous studies have begun to address this question at the state-government level [e.g., Rashid et al, 2010] and at the city-government level [e.g., Gerrity and Snyder, 2011;Teodoro, 2010]. We build on this approach by providing both quantitative and qualitative analyses that draw on both hydrological and social science perpsectives.…”
Section: 1002/2015wr016943mentioning
confidence: 99%
“…For example, Mullin () found that mean daily maximum temperature, proportion of retail sales, population, and location in the Western and Midwestern regions of the U.S. are positively associated with the presence of an increasing block‐rate pricing structure (a policy that increases the price per unit of water as the consumer uses more water). Teodoro () found that the number of customer connections, aridity (climate‐moisture index), and peak‐to‐average demand ratio are associated with the adoption of an increasing block‐rate structure, but peak‐to‐average demand ratio was not significant for the prediction of landscape audit programs. Both researchers found that variations in governance structures can also affect the adoption of WCPs.…”
Section: Introductionmentioning
confidence: 97%
“…They have also pointed to important differences among the type of WCP, such as landscape audits vs . an increasing block rate structure (Teodoro, ) and pricing vs . demand‐management policies (Aubuchon and Roberson, ).…”
Section: Introductionmentioning
confidence: 99%
“…Before developing a new measure of rate progressivity, it is important to first understand the basic typology of water rate structures. There are many varieties of rate structures, but they can most easily be grouped into five basic types (Teodoro, ): Flat rates : This rate structure charges all customers the same price for a fixed time period, regardless of the amount of water consumed. This rate structure does not require metering and is therefore less costly from an administrative perspective. Uniform rates : This rate structure charges all customers the same price per unit of water, regardless of the amount of water consumed. Decreasing block rates : This rate structure charges higher prices per unit for low‐volume users than for high‐volume users.…”
Section: Types Of Water Ratesmentioning
confidence: 99%